Additive interactions between obesity and insulin resistance on hypertension in a Chinese rural population - Xiaoxia Li; Xiaoyu Chang; Yuanyuan Dang; Yixuan Xue; Qingan Wang; Wanlu Liu; Ting Yin; Yi Zhao; Yuhong Zhang (BMC, 2023)
Abstract Background Adiposity and insulin resistance (IR) are closely associated with hypertension; however, the role of interactions between obesity phenotypes and IR in hypertension is unclear. This study aimed to evaluate the interactions of body mass index (BMI), waist circumference (WC), and body fat percentage (BF%) with IR on hypertension risk. Methods We analyzed data from 4888 participants (mean age 57 years, 41.2% men) in the China Northwest Natural Population Cohort, Ningxia Project. BMI, WC, and BF% were determined using bioelectrical impedance analysis devices. IR was estimated using a homeostasis model assessment index (HOMA-IR). Multivariable-adjusted logistic regression was used to evaluate the association between HOMA-IR and hypertension risk. We calculated the relative excess risk and attributable proportion with their 95% confidence intervals (CIs) to assess whether adiposity phenotypes modified the effect of HOMA-IR on hypertension risk. Results The crude prevalence of hypertension was 52.2%. The multivariable-adjusted odds ratio of HOMA-IR was 1.80 (95% CI: 1.23-2.65) for the risk of hypertension in the highest versus the lowest quartiles, but this association became marginal in models further adjusting for BMI, WC, and BF% (P for trend = 0.056). Relative excess risk and attributable proportion for interaction between high HOMA-IR and high BF% were 0.32 (0.04-0.59) and 0.33 (0.06-0.60), respectively. Additionally, high truncal and leg BF% and high HOMA-IR accounted for the hypertension risk in women, but not in men. We did not observe any significant interactions between BMI or WC and HOMA-IR on hypertension. Conclusion BF% modified the association between IR and increased risk of hypertension in women with high truncal and leg BF%, but not in men.